MANAJEMEN PEMBELAJARAN STRATEGI MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH PERTAMA - sariman Sariman (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
This study describes and analyzes the implementation of learning management at SMP Al Muhammad Cepu. This research uses a qualitative descriptive approach with field studies. The subjects of this study were school principals, head of curriculum and teachers of SMP Al Muhammad Cepu. It was found that learning management: the learning management abilities of Al Muhammad Cepu Middle School teachers in the planning aspect were carried out through a study planning IHT review. Improving literacy in reading various reading sources in the library, participating in training, seminars and upgrading. In the aspect of implementing or implementing learning, the efforts made by the teacher are reading various reading sources (literature) related to learning material, studying the syllabus that will be taught, attending training, seminars and upgrading, and opening the internet. In the evaluation aspect, the effort made by the teacher is to read various reading sources (literature). The school's efforts to improve the quality of education at SMP Al Muhammad Cepu through learning management are to provide educational facilities that are adequate and relevant to learning needs, provide space and awards for outstanding teachers, by holding outstanding teachers, teacher creativity competitions, promotions.